2005
DOI: 10.1128/jb.187.20.6902-6908.2005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Thermophilic ATP-Dependent DNA Ligase from the Euryarchaeon Pyrococcus horikoshii

Abstract: Archaea encode a DNA ligase composed of a C-terminal catalytic domain typical of ATP-dependent ligases plus an N-terminal domain similar to that found in eukaryotic cellular and poxvirus DNA ligases. All archaeal DNA ligases characterized to date have ATP-dependent adenylyltransferase and nick-joining activities. However, recent reports of dual-specificity ATP/NAD ؉ ligases in two Thermococcus species and Pyrococcus abyssi and an ATP/ADP ligase in Aeropyrum pernix raise the prospect that certain archaeal enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 28 publications
(44 reference statements)
3
25
0
Order By: Relevance
“…This result is the same as in the case of DNA ligase from Pyrococcus horikoshii in a recent report (21). We think that the ligation reaction may be derived from contaminant ATP (1.16%) in our ADP reagent (Oriental Yeast Co., Ltd., Osaka, Japan) according to the manufacturer's certificate, and therefore, we concluded that ADP is not an appropriate cofactor for PfuLig, as Keppetipola and Shuman (21) described for P. horikoshii DNA ligase.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This result is the same as in the case of DNA ligase from Pyrococcus horikoshii in a recent report (21). We think that the ligation reaction may be derived from contaminant ATP (1.16%) in our ADP reagent (Oriental Yeast Co., Ltd., Osaka, Japan) according to the manufacturer's certificate, and therefore, we concluded that ADP is not an appropriate cofactor for PfuLig, as Keppetipola and Shuman (21) described for P. horikoshii DNA ligase.…”
Section: Resultssupporting
confidence: 89%
“…In Archaea, the third domain of life, a single homolog of eukaryotic Lig I has been identified (17)(18)(19)(20)(21). Interestingly, although most of the archaeal replicative enzymes have a eukaryotic PIP box at their C termini, no clear PCNA-binding motif has been observed in the sequences of archaeal DNA ligases (5,22).…”
mentioning
confidence: 99%
“…Phylogenetic analysis of the sequences presented here is consistent with previous studies of DNA ligases (Nakatani et al 2000). However, the addition of amino acid sequences for FaLig and related enzymes from other Thermoplasmatales identified that these are more similar to DNA ligases that have been characterized from Crenarchaeota (Jeon and Ishikawa, 2003;Kletzin 1992;Lai et al 2002) compared to those from Euryarchaeota (Gunther et al 2002;Keppetipola and Shuman 2005;Nakatani et al 2000;Rolland et al 2004;Sriskanda et al 2000;Zhao et al 2006). This phylogenetic description suggests that lateral gene transfer has occurred in the evolution of the DNA ligases of the Euryarchaeota.…”
Section: Biochemical Characterization Of Nick-joining By Faligsupporting
confidence: 89%
“…The pH profile of FaLig is similar to that observed for a variety of DNA ligases, but it is now clear that the optimal pH for activity varies for enzymes from different organisms. In terms of archaea that grow at neutral pH, the optimal activity of their DNA ligases has been detected to be pH 7-8.5 (Jeon and Ishikawa 2003;Keppetipola and Shuman 2005;Rolland et al 2004;Sriskanda et al 2000). For DNA ligase from S. shibatae, which is able to grow at pH 2-4, optimal nickjoining was detected at pH 6-7 (Lai et al 2002).…”
Section: Biochemical Characterization Of Nick-joining By Faligmentioning
confidence: 99%
“…Biochemical characterization of several archaeal DNA ligases verified their strict dependence on ATP and failure to utilize NAD ϩ (summarized in Ref. 22). By contrast, other archaeal ligases were reported to have "dual specificity," variously using ATP and NAD ϩ or ATP and ADP (supplemental Fig.…”
Section: Is There An "Undifferentiated" Ligase With Respect To the Sumentioning
confidence: 81%